2003
DOI: 10.1051/gse:2003043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of�meat technological quality traits in�a�grand-parental commercial line of�turkey

Abstract: -Genetic parameters for meat quality traits and their relationships with body weight and breast development were estimated for a total of 420 male turkeys using REML. The birds were slaughtered in a commercial plant and the traits measured included pH at 20 min (pH 20 ) and 24 h post-mortem (pHu) and colour of the breast and thigh meat. The heritabilities of the rate and the extent of the pH fall in the breast muscle were estimated at h 2 = 0.21 ± 0.04 and h 2 = 0.16 ± 0.04, respectively. Heritabilities rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
3
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 16 publications
3
19
3
7
Order By: Relevance
“…Higher lightness values in HG line could also result from a lower pHu. This is consistent with the negative phenotypic relationship (-0.24) found between breast meat ultimate pH and lightness in the F2 population and in other studies reporting strong negative genetic correlations of -0.91 in the chicken [6] and of -0.53 in the turkey [7]. In chicken breast meat, the ultimate pH depends on muscle glycogen-equivalent content at death [5].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Higher lightness values in HG line could also result from a lower pHu. This is consistent with the negative phenotypic relationship (-0.24) found between breast meat ultimate pH and lightness in the F2 population and in other studies reporting strong negative genetic correlations of -0.91 in the chicken [6] and of -0.53 in the turkey [7]. In chicken breast meat, the ultimate pH depends on muscle glycogen-equivalent content at death [5].…”
Section: Discussionsupporting
confidence: 79%
“…Stress and behavioral activity on the pre-slaughter shackle line and muscle glycogen content at slaughter time have been shown to be involved in the variations of pH15 and pHu [4,5]. High heritability (h 2 ) values were observed for several meat quality traits in chickens (h 2 = 0.35 to 0.57) slaughtered under controlled experimental conditions [6] and in turkeys (h 2 = 0.12 to 0.21) slaughtered under commercial conditions [7]. Therefore, these traits could be efficiently improved by phenotypic selection.…”
Section: Introductionmentioning
confidence: 87%
“…An inverse and moderate correlation of -0.30 found between pH24 and L* suggests that the meat of the studied strain tends to present greater lightness when the pH24 is smaller, indicating the occurrence of protein denaturation 24 hours after slaughter. This is in agreement with the results of LE BIHAN-DUVAL et al (2003), who reported that the greater the degree of protein denaturation, the less the amount of light transmitted through the fibers and the more light that is dispersed, which makes the meat pale. DEBUT et al (2003) also found negative and moderated correlations between the lightness of the meat and the pH 24 hours after slaughter.…”
Section: Resultssupporting
confidence: 82%
“…The poultry market has excelled in the production of noble carcass parts and processed products (Le Bihan-Duval et al, 2003). Therefore, intense selection for these traits may have also led to changes in meat quality attributes, such as tenderness in particular (Dransfield and Sosnicki, 1999).…”
Section: Introductionmentioning
confidence: 99%